Pemberdayaan Keterampilan Literasi Matematika melalui Metode Picture and Picture pada Siswa Sekolah Dasar - Alberth Supriyanto Manurung; Abdul Halim (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
he community service activity aimed to enhance students' mathematical literacy skills using the Picture and Picture (PnP) method. The PnP method is a method that supports students' success in solving learning problems, especially in mathematics lessons. The PnP method can create students' sense of knowledge visually or with real images, which students really need in creating an ideal learning atmosphere so that students can directly experience the visuals of mathematics lessons. The method used in this activity is in the form of a lecture by providing counseling on how to learn using the PnP method so as to improve students' skills in solving mathematical problems. Students are given counseling using PowerPoint and video media. Then participants were given the opportunity to ask questions and then 4 discussion groups were formed to discuss problems related to how to learn using the PnP method. The activity took place on Monday, May 20 2024, participants were students of SDN Duri Kepa 03 West Jakarta. From the pre-test results through questions and answers from 30 students, knowledge about the Picture and Picture method was still in the poor category, while the post-test results showed an increase in knowledge of around 82% of students with a good level of knowledge.